2005
DOI: 10.1191/0269215505cr906oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of external rhythmical cueing on gait in patients with Parkinson's disease: a systematic review

Abstract: Only one high-quality study, specifically focused on the effects of auditory rhythmical cueing, suggesting that the walking speed of patients with Parkinson's disease can be positively influenced. However, it is unclear whether positive effects identified in the laboratory can be generalized to improved activities of daily living (ADLs) and reduced frequency of falls in the community. In addition, the sustainability of a cueing training programme remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
308
3
15

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(348 citation statements)
references
References 39 publications
9
308
3
15
Order By: Relevance
“…studies have shown that rhythmic auditory stimulation (RAS) can improve the spatiotemporal features of gait in patients with PD (Lim et al, 2005;Rubenstein, Giladi, & Hausdorff, 2002). When using RAS, administered in the form of a metronome, gait speed and stride length improved in PD patients both at 'on' and 'off' states (McIntosh, Brown, Rice, & Thaut, 1997;Willems et al, 2006).…”
Section: Rhythmic Auditory Stimulation (Ras) Improves Gait Rhythmicitmentioning
confidence: 99%
“…studies have shown that rhythmic auditory stimulation (RAS) can improve the spatiotemporal features of gait in patients with PD (Lim et al, 2005;Rubenstein, Giladi, & Hausdorff, 2002). When using RAS, administered in the form of a metronome, gait speed and stride length improved in PD patients both at 'on' and 'off' states (McIntosh, Brown, Rice, & Thaut, 1997;Willems et al, 2006).…”
Section: Rhythmic Auditory Stimulation (Ras) Improves Gait Rhythmicitmentioning
confidence: 99%
“…By providing an external clock that helps to set the pace and comes in place of the impaired internal rhythmicity in PD, RAS can apparently improve, at least in the short term, many of the spatiotemporal features of gait in patients with PD. [118][119][120][121] When using RAS, administered in the form of a metronome, gait speed and stride length generally increase ͑become more normal͒ in PD patients, both in the on and off states. 122 When RAS is administered at a rate either equal to the patients' baseline step rate ͑cadence͒ or 10% higher, double support time is reduced and stride length increases.…”
Section: Effects Of Rhythmic Auditory Stimulationmentioning
confidence: 99%
“…It is well recognized that auditory, visual, or tactile stimuli can improve gait in patients with PD [2]. As a result, devices that exploit the sensory cueing-related modification of gait in patients with PD have been proposed with limited success for ongoing use [3][4].…”
Section: Introductionmentioning
confidence: 99%